2019
DOI: 10.1155/2019/5689613
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Cartilage Destruction by Sinapic Acid in Experimental Osteoarthritis

Abstract: Sinapic acid (SA) modulates the nuclear factor-erythroid 2-related factor 2 (Nrf2) signaling pathway in chondrocytes. In order to test the hypothesis that SA is protective against the development of osteoarthritis (OA), primary mouse chondrocytes were treated in vitro with SA and the promoter transactivation activity of heme oxygenase 1 (HO-1), nuclear translocation of Nrf2, and protein expression of HO-1 were assayed. To test the hypothesis in vivo, a destabilization of the medial meniscus (DMM) model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Sinapic acid possesses anti-inflammatory effects through subduing manifestation of COX-2, iNOS, and TNF-α. 28 Chlorogenic acid (CA) is a polyphenol. Various studies have shown that CA exhibits different pharmacological effects like immunoprotective, anti-inflammatory, and antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Sinapic acid possesses anti-inflammatory effects through subduing manifestation of COX-2, iNOS, and TNF-α. 28 Chlorogenic acid (CA) is a polyphenol. Various studies have shown that CA exhibits different pharmacological effects like immunoprotective, anti-inflammatory, and antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Given its antioxidant properties, several studies have suggested a protective role of HO-1 in OA pathogenesis. It has been reported that HO-1 is significantly upregulated in human and mouse models of OA, with higher levels of expression being observed in areas of cartilage damage [ 120 , 121 ]. However, discrepancies exist regarding Nrf2/HO-1 expression between OA cartilage and IL-1β-induced OA-like chondrocytes [ 122 , 123 ].…”
Section: The Role Of Heme Oxygenase-1 In Arthritismentioning
confidence: 99%
“…Although there was no significant statistical difference in the expression of both Nrf2 and HO-1 between the OA/CFA group and the Control/CFA group (may be due to the limited number of samples), it was speculated that the level of HO-1, a member of heat shock protein (HSP) family, which is produced by cells in response to exposure to stressful conditions, may be much higher in the OA/CFA group compared with the Control/CFA group. In our previous study, it was found that the level of HO-1 in knee cartilage significantly increased in both patients with OA and DMM-induced OA mice relative to controls, which may be regarded as a beneficial adaptive response to oxidative stress in chondrocytes during the progression of OA ( 20 ). These findings suggested that the development of OA also contributed to the increased expression of HO-1 in the OA/CFA group, and the very obvious upregulation of HO-1 induced by CFA may play a key role in delaying the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…HO degrades heme to free iron, biliverdin and carbon monoxide ( 21 ). The authors previously reported that HO-1 expression is increased in cartilage from patients diagnosed with OA, which is regarded as an adaptive response against stress during cartilage damage ( 20 ). The induction of HO-1 suppresses the IL-1-induced expression of MMPs and inflammatory factors ( 22 , 23 ), which are abnormally enhanced in OA-affected cartilage.…”
Section: Discussionmentioning
confidence: 99%